Modèles de structures informationnelles globales de discours - Miczka, Ewa (Neophilologica, 2011)
The aim of this paper is to analyze the types of global organisation of information structures in discourse. Information structures are defined as hierarchically organized thematic-rhematic structures and, in their thematic part, the author distinguishes three levels represented by: global theme, theme of a group of sentences and sentence theme. The author focuses her attention on two highest levels of information structure and describes the models of global information structure.